(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
When the oil production of the hydraulically fractured well A-1 began to decline, a refracturing of the well was planned, as a reduction in the fracture size was assumed after a long production period. Several possibilities of the pressure build-up test analyses were performed to determine the best evaluation of the reduced fracture half-length. Although the objectives of these tests are to determine the reservoir properties, such as rock permeability and skin factor, as well as fracture conductivity, the Saphir programme is also used to model the fracture half-length. This is the most important parameter required for the design of the new fracturing process and for the creation of a new production model. For this purpose, the methods of the pressure build-up test analysis are first described theoretically. Based on different analyses of the same pressure build-up test, the one that best matches the analytical model of a fractured well with the measured pressure curve and the derivative curve is selected. It is found that the most accurate result for fracture half-length is obtained from the fractured well model with multiphase flow.